Biosimilars for the treatment of patients with psoriasis: A consensus statement from the Biosimilar Working Group of the International Psoriasis CouncilCapsule Summary - Arnon D. Cohen, MD, MPH, PhD; Ronald Vender, MD, FRCPC; Luigi Naldi, MD; Robert E. Kalb, MD; Tiago Torres, MD, PhD; Murlidhar Rajagopalan, MD; Joelle van der Walt, PhD; Lluís Puig, MD (Hon), PhD; Helen S. Young, MB ChB, PhD, FRCP (JAAD International, 2020)
Background: As biosimilars have become available in various parts of the world, the International Psoriasis Council has reviewed aspects of their use. Objective: To provide consensus statements from the Biosimilar Working Group about the use of biosimilars in patients with psoriasis. Methods: A semiqualitative structured process was employed to approve the consensus statements on biosimilars using the nominal group technique. The final statements were validated by a survey of the paricipants. The approval of the consensus statements was predefined as >80% positive opinions. Results: A consensus was reached in 36/38 statements regarding regulatory considerations, extrapolation of indication, interchangeability, substitution at the pharmacy level, pharmacovigilance, traceability, naming, biosimilar policy, education, and cost of biosimilars. Example statements include “Switching a stable patient from a reference product to a biosimilar product is appropriate if the patient and physician agree to do so” and “Patients and patients' organisations should be involved in all decision making and policy development about the use of biosimilars.” Conclusion: The International Psoriasis Council Biosimilar Working Group provides consensus statements for the use of biosimilars in the treatment of patients with psoriasis. We suggest that these statements provide global guidance to clinicians, healthcare organizations, pharmaceutical companies, regulators, and patients regarding the development and use of biosimilars in patients with psoriasis.